Model Predictive Control Using Subdivided Voltage Vectors for Current Ripple Reduction in an Indirect Matrix Converter - Kim, Keon Young; Bak, Yeongsu; Park, Jin Hyuk; Lee, Kyo Beum (2018 International Power Electronics Conference, IPEC-Niigata - ECCE Asia 2018, 2018)
This paper proposes a model predictive control (MPC) using subdivided voltage vectors for current ripple reduction in an indirect matrix converter (IMC). In the proposed MPC, the number of candidate voltage vectors is increased by the subdivided voltage vectors. It is possible to reduce the input-output current ripple of the IMC. In addition, the proposed MPC reduces computation load, which is caused by the subdivided voltage vectors, by estimating the position of reference voltage vector. Therefore, the input-output current ripple of the IMC is reduced by the proposed MPC without computational burden. The effectiveness of the proposed MPC is verified by simulation results.
Keywords: Computation loads; Computational burden; Current-ripple reduction; Finite set; Indirect matrix converter; Indirect matrix converter (IMC); Reference voltages; Voltage vectors; current ripple reduction; finite set model predictive control; indirect matrix converter; subdivided voltage vector